Identifying characteristics of non-completers in fear conditioning paradigms with children and adolescents. Issue 2 (7th July 2022) - Flasinski, Tabea; Sommer, Katharina; Schneider, Silvia; Margraf, Jürgen; Pflug, Verena; Lippert, Michael W; Christiansen, Hanna; Cwik, Jan C; Hamm, Alfons O; In-Albon, Tina; Knappe, Susanne; Pauli, Paul; et al.
The number of studies on fear conditioning in children and adolescents has increased in recent years. Most of these studies exclusively focus on data of completers while dropout rates, reasons for dropout, and specific characteristics of non-completers are underreported. This study systematically investigated data of 283 children and adolescents between 8 and 17 years ( M = 11.10, SD = 2.14) undergoing a differential fear conditioning paradigm using a female scream as unconditioned stimulus (US). The sample included 230 children and adolescents with a current primary anxiety disorder (separation anxiety disorder, social anxiety disorder, and specific phobia) and 53 non-anxious controls. The dropout rate was 24.1%. The most common reason to discontinue was being afraid of the US (59.1%) followed by the startle probe being too loud (15.2%). Logistic regressions revealed that younger age and a present anxiety disorder predicted dropout. There seem to be distinct characteristics potentially predicting dropout from fear conditioning paradigms. Thus, interpretability and generalizability of those paradigms are limited when non-completers are not considered. Future research should conscientiously look at these data more closely and investigate paradigms that work independent of age and diagnostic status.